Hand-held fan airflow stimulation relieves dyspnea in lung cancer patients - Ni Luh Putu Dewi Puspawati; Ratna Sitorus; Tuti Herawati (Elsevier, 2017)
Objective: The main symptom of lung cancer is dyspnea which can lead to depression, anxiety, limited independent activities, and decreased quality of life. The purpose of this study was to identify the effect of airflow stimulation from a hand-held fan as nonpharmacological palliative intervention on dyspnea in patients with lung cancer. Methods: This study used open, randomized, controlled, crossover trial design involved 21 participants. Diaphragmatic breathing technique was used in control arm. Results: Wilcoxon test result showed that airflow stimulation significantly influenced dyspnea scale (P = 0.003) and respiratory rate (RR) (P = 0.008). Combination of airflow stimulation and diaphragmatic breathing can lower both dyspnea scale and RR significantly (P < 0.0001). Conclusions: This combination can be applied on nonhypoxemic dyspneic lung cancer patients.